The impact of Aureobasidium melanogenum cells and extracellular vesicles on human cell lines - Anja Černoša; Cene Gostinčar; Marija Holcar; Rok Kostanjšek; Metka Lenassi; Nina Gunde-Cimerman (Scientific Reports)
Abstract Aureobasidium melanogenum is a black yeast-like fungus that occurs frequently both in nature and in domestic environments. It is becoming increasingly important as an opportunistic pathogen. Nevertheless, its effect on human cells has not yet been studied. In this study, we investigated the effect of A. melanogenum cells and extracellular vesicles (EVs) on human cell lines A549 (human lung cells), HDFa (human dermal fibroblasts), and SH-SY5Y (human neuroblastoma cells). Scanning electron microscopy (SEM) showed no direct interaction between A. melanogenum cells and human cell lines, but there were some changes in HDFa cells. As a possible cause for this change, we tested the cytotoxic effect of EVs from A. melanogenum on the same cell lines. We isolated EVs from the fungus and prepared three different pools: a non-melanin pool (containing mainly EVs), a melanin pool (containing mainly melanin nanoparticles), and a total pool (containing both EVs and melanin nanoparticles). All three pools were characterized and then added to human cell lines to test their cytotoxicity. Unlike in some other fungal opportunistic pathogens, no effects of fungal EVs on human cell viability were observed. Therefore, the opportunistic potential of A. melanogenum remains only partially understood.